A multi-aromatic hydrocarbon unit induced hydrophobic metal–organic framework for efficient C2/C1 hydrocarbon and oil/water separation. Issue 3 (20th December 2016) - Zhang, Minghui; Xin, Xuelian; Xiao, Zhenyu; Wang, Rongming; Zhang, Liangliang; Sun, Daofeng
Abstract : A highly hydrophobic Cu(ii ) MOF (UPC-21 ) was synthesized through a newly developed "diauxic growth" strategy. The multi-aromatic hydrocarbon units in the framework are responsible for hydrophobic character ofUPC-21 . Its application on water purification and oil/water separation was studied for the first time. Abstract : Oil spills have led to more and more energy waste and economic losses all over the world. Developing highly hydrophobic materials for efficient oil/water separation has become key in solving this global issue. Here we report a highly hydrophobic porous metal–organic framework, namedUPC-21, constructed from a pentiptycene-based organic ligand, for efficient oil/water separation. Large and pure crystals ofUPC-21 could be obtained with high yield through a developed "diauxic growth" strategy. Due to the existence of multi-aromatic hydrocarbon units in the central pentiptycene core of the ligand, UPC-21 exhibits high hydrophobicity with a water contact angle of 145 ± 1° and superoleophilicity with an oil contact angle of 0°. Strikingly, oil/water separation measurements reveal thatUPC-21 can efficiently separate toluene/water, hexane/water, gasoline/water, naphtha/water, and crude oil/water with a separation efficiency being above 99.0% except for crude oil/water due to its high viscosity and complex composition. Our work presented here may open a new avenue for the application of porous MOF materials.